A Case Study of Hemochromatosis and Conflicting Point Shear Wave Measurements in the Assessment of Liver Fibrosis. Issue 1 (March 2017) - Cohen, Tal; Barr, Richard G.
Abstract : Abstract: There are multiple factors that affect the shear wave speed in the assessment of liver stiffness. In this case report, we present a case of hemochromatosis that has elevated liver stiffness suggestive of significant fibrosis or cirrhosis; however on liver biopsy, no fibrosis was identified. This article will discuss the possibility that liver iron deposition may affect SWE measurements of the liver, leading to inaccurate assessment of liver fibrosis. In these cases, a liver biopsy may be required for accurate liver assessment.